A case of pulmonary melioidosis in Germany: a rare differential diagnosis in returning travelers from South-East Asia - Gottschalk, Claudius; Stojković, Marija; Zangenfeind, Sabine; Wolf, Peter; Klein, Julian (Infection, 2024)
Melioidosis is a bacterial infection associated with high mortality. The diagnostic approach to this rare disease in Europe is challenging, especially because pulmonary manifestation of melioidosis can mimic pulmonary tuberculosis (TB). Antibiotic therapy of melioidosis consists of an initial intensive phase of 2-8 weeks followed by an eradication therapy of 3-6 months.
Gesehen am 15.08.2024